Cysteinyl leukotrienes and 8-isoprostane in exhaled breath condensate of children with asthma exacerbations. Issue 6 (1st June 2003) - Baraldi, E; Carraro, S; Alinovi, R; Pesci, A; Ghiro, L; Bodini, A; Piacentini, G; Zacchello, F; Zanconato, S
Abstract : Background: Cysteinyl leukotrienes (Cys-LTs) and isoprostanes are inflammatory metabolites derived from arachidonic acid whose levels are increased in the airways of asthmatic patients. Isoprostanes are relatively stable and specific for lipid peroxidation, which makes them potentially reliable biomarkers for oxidative stress. A study was undertaken to evaluate the effect of a course of oral steroids on Cys-LT and 8-isoprostane levels in exhaled breath condensate of children with an asthma exacerbation. Methods: Exhaled breath condensate was collected and fractional exhaled nitric oxide (FENO ) and spirometric parameters were measured before and after a 5 day course of oral prednisone (1 mg/kg/day) in 15 asthmatic children with an asthma exacerbation. Cys-LT and 8-isoprostane concentrations were measured using an enzyme immunoassay. FENO was measured using a chemiluminescence analyser. Exhaled breath condensate was also collected from 10 healthy children. Results: Before prednisone treatment both Cys-LT and 8-isoprostane concentrations were higher in asthmatic subjects (Cys-LTs, 12.7 pg/ml (IQR 5.4–15.6); 8-isoprostane, 12.0 pg/ml (9.4–29.5)) than in healthy children (Cys-LTs, 4.3 pg/ml (2.0–5.7), p=0.002; 8-isoprostane, 2.6 pg/ml (2.1–3.0), p<0.001). After prednisone treatment there was a significant decrease in both Cys-LT (5.2 pg/ml (3.9–8.8), p=0.005) and 8-isoprostane (8.4 pg/ml (5.4–11.6), p=0.04) concentrations, but 8-isoprostane levels remained higher than in controls (p<0.001). FENO levels, which fell significantly after prednisone treatment (p<0.001), did not correlate significantly with either Cys-LT or 8-isoprostane concentrations. Conclusion: After a 5 day course of oral prednisone there is a reduction in Cys-LT and 8-isoprostane levels in EBC of children with an asthma exacerbation, although 8-isoprostane levels remain higher than in controls. This finding suggests that corticosteroids may not be fully effective in reducing oxidative stress in children with an exacerbation of asthma.